Power-to-Gas Renewable Hydrogen Economy for the Energy Transition - Boudellal, Méziane (De Gruyter, 2018)
With the development of renewable electricity and the expected important surpluses of production, how can the use of hydrogen improve the green energy portfolio? Power-to-Gas covers the production of hydrogen through electrolysis and its storage or conversion in another form (gas, chemicals or fuels). It emphasises the need for new technologies with global energy consumption, markets, and logistics concepts. Pilot projects around the world are discussed as well as how policy and economics influence the real use of these energy harvesting and conversion technologies.